Redesign taman Kota Tabanan Kabupaten Tabanan, Bali - Ni Wayan Chili Jayanthi; I Made Sukewijaya; Anak Agung Gede Sugianthara (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Tabanan City Park is located around settlements and main road, yet the park seems deserted at certain times. It is revealed that most of the park’s surface has construction residual materials, lack of basic facilities, and the plants were not maintained. This study aims to identify the existing condition of the park, and create a redesign concept of the park, with consideration of people’s perceptions and preferences regarding the comfort they feel when they are in the park. This study uses survey research methods. After analysing the data, a synthesis was made to compose a redesign concept that able to increase the beauty, comfort and safety of Tabanan City Park. The main concept of this study is “Open Space for All”, meaning an open space for all positive activity that caters to all levels of society. The concept of space in this study is divided into 3 (three) spaces, namely reception space, passive, and active engagement space. Facilities added to the design are hardscapes such as children’s playground, outdoor gym, and toilets, also softscape such as flower beds, shrubs, and shade trees.